Analysis of Print Media and its Future Outlook - Naumkina, Anna; Cook, Gina, 1970-; Štěrbová, Ludmila, 1957-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2016)
The thesis is focused on analyzing the development of print media based on the example of selected fashion magazines. It is also focused on the international strategies that can be used by these magazines. The author examines the theoretical background of print media and international marketing strategies, followed by application of this knowledge on the analysis of the chosen magazines. The thesis consists of two main parts: theoretical and empirical. The theoretical part includes a description of print media history, the background of magazines, and international marketing communications, particularly with regard to magazines. The empirical part is focused on analysis of the selected magazines and their international strategies. This part concentrates on the printed and online versions of magazines, so it is easier to see how magazines are influenced by new technologies.
Vedoucí práce: Gina Cook
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2016
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2016
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses